Analisis Konflik Sosial, Legal dan Finansial dalam Studi Kelayakan Usaha Kemitraan Kebun Sawit Rakyat: Studi Kasus Konflik Agraria KKPA Bongkal Malang, Kabupaten Indragiri Hulu, Provinsi Riau - Prima Sani Nasution, Zulfi; Nurkhoiry, Ratnawati; Rahmat Syahputra, Agung (Jurnal Penelitian Kelapa Sawit, 2023)
The expansion of smallholder oil palm plantations in Riau has not only had a positive impact on the economy but has also been followed by an increase in agrarian conflict cases. This research tries to contribute ideas in efforts to overcome agrarian conflicts in oil palm plantations, especially in the KKPA scheme which still lacks systematic analysis from a social, legal, and financial perspective. This research focuses on a case study of agrarian conflict in KKPA Bongkal Malang, Indragiri Hulu Regency, Riau, where no conflict resolution mechanism has been found to date. The findings of this research indicate that the agrarian conflict of KKPA Bongkal Malang can be categorized as a critical and wide-scale social conflict, with significant negative impacts on social and economic aspects for both parties. Regulatory changes led to a mismatch in the legality of the Bongkal Malang KKPA partnership with new legal provisions, creating uncertainty in investment. The unresolved conflict also made the financial viability of the partnership unviable. The analysis concludes that continuing the Bongkal Malang KKPA partnership is not feasible, and conflict resolution is a top priority. The resolution of this conflict requires political support and political will from the central and local governments, with a negotiation-mediation or reconciliation-cooperation approach considered the most appropriate mechanism, ensuring a fair solution for all parties involved.